Globalization and emerging societies : development and inequality - Pieterse, Jan Nederveen (ed.); Rehbein, Boike (ed.) (Hampshine, 2009)
This book brings a sociological perspective to the study of emerging economies and newly-industrializing countries in emerging societies. Rather than being naively optimistic about the rise of major countries in the South such as China, India and Brazil, the book focuses on development and social inequality in the emerging societies. Each chapter focuses on development and social inequality in emerging societies and, set within the context of 21st century globalization$1 (Bin marked contrast to 20th century globalization$1 (Bthe book develops this phase of globalization as a theme. s
Keywords: Globalization